Effectiveness of Multimedia Based on Education and Traditional Methods on Life Quality of Hemodialysis Patients - Hossein Feizalahzadeh; Mansoureh Zagheri Tafreshi; Hamid Moghaddasi; Mansoureh Ashghali Farahani; Zahra Zareh; MohammadReza Khalilzadeh (Journal of Holistic Nursing and Midwifery)
Introduction:Hemodialysis patients require effective education to improve their quality of life. Flexible educational strategy via internet (computer) is essential